Grain-boundaries-engineering via laser manufactured La-doped BaSnO₃ nanocrystals with tailored surface states enabling perovskite solar cells with efficiency of 23.74% - Yang, Xiaokun (2022)
Grain boundaries (GBs) engineering of hybrid perovskite films is of significance for accessing high performance perovskite solar cells (PSCs), owing to the abundant defect states existed therein originating from the low temperature film processing. Nanocrystals embedding at GBs has shown profound advantages in carrier dynamics modulation, while the surface defects on nanocrystals in turn lead usually to the trapping of carriers at GBs. The authors herein demonstrate the efficient GBs engineering via laser generated nanocrystals with tailored surface states for improved carriers dynamics and environmental stability of PSCs. The embedding of La doped BaSnO3 (LBSO) nanocrystals with bare surfaces in perovskite provides an additional channel to facilitate the effective carrier extraction and reduce the carrier recombination, leading to a maximum power conversion efficiency (PCE) of 21.11% with negligible hysteresis for the mixed-cation PSCs. To clarify the influence of surface defect states of the laser generated nanocrystals on the performance of PSCs, 1H,1H-perfluorooctylamine is grafted on LBSO nanocrystals during the laser irradiation, resulting in improved champion PCE up to 21.65% and pronounced environmental stability. The universal embedding of the LBSO nanocrystals with tailored surface states in different perovskite by fabricating FAPbI3 PSCs with a champion PCE of 23.74% is further demonstrated.